THE EFFECT OF NONI LEAF (Morinda Citrifolia Linn.) WATER EXTRACT OF LOHMANN BROWN LAYING HEN ON PROTEIN, FAT AND CHOLESTEROL CONTENT IN EGG YOLK - M., Arki; Bidura, I G. N. G.; Utami, I. A. P. (Jurnal Peternakan Tropika, 2019)
This study aim was to find out the effect of noni leaf ( Morinda Citrifolia Linn.) water extract given into drinking water to protein, fat and cholesterol of chicken egg yolk of Lohmann Brown . Research at Dajan Peken Village, Tabanan sub-district-Bali for 3 months with 36 Lohmann Brown chicken the age 22-30 weeks. The method used in this research is Completely Randomized Design (CRD) with 3 treatments and 6 replications. The treatment: without water extract of noni leaf ( Morinda Citrifolia Linn.) As a control (M0); 2% noni leaf water extract (M1) and 4% noni leaf water extract (M2). The variables observed in this study were egg yolk protein, fat content and egg yolk cholesterol levels. The results obtained were tested by multiple analyisis from Duncan. The results showed that giving noni water extract as much as 2% and 4% can increase the protein content of chicken egg yolk, decreased fat and cholesterol levels of Lohmann Brown chicken egg yolk 22-30 weeks. Keywords: Lohmann Brown chicken, noni leaf, egg yolk